"Facts, Not Fear": Negotiating Uncertainty on Social Media During the 2014 Ebola Crisis. (August 2016) - Dalrymple, Kajsa E.; Young, Rachel; Tully, Melissa
Trust in many government organizations is low, creating a challenging environment for communication during outbreaks of emerging infectious diseases, like Ebola. In a thematic analysis of 1, 010 tweets and four Twitter chats during the 2014-2015 Ebola outbreak, we found that the Centers for Disease Control and Prevention emphasized organizational competence, extant protocol, and facts about transmission to manage public fear. We argue that an emphasis on certainty in a rapidly changing situation leaves organizations vulnerable to charges of unpreparedness or obfuscation. Our results also speak to the contested definition of engagement online, particularly during health crises.